Construction of binary metal sulphides via lignosulfonate as sulphur source for efficient oxygen evolution reaction. (26th March 2023) - Ma, Zihao; Han, Ying; Wang, Qingyu; Wang, Xing; Sun, Guangwei; Li, Yao
Abstract: Due to its slow kinetics, the oxygen evolution reaction (OER) is a key limiting reaction in electrocatalytic water separation and fuel cells. Transition metal sulphides with high intrinsic activity, outstanding stability and excellent electrical conductivity have been considered as promising electrocatalysts for OER. In this study, we develop a green and general strategy for the synthesis of nitrogen, sulphur co-doped honeycomb like carbon nanosheets coupled with binary metal sulfides ((M 1, M 2 ) x S y @SNC, (M 1, M 2 ) = Fe, Co, Ni) derived from chitosan (nitrogen sources) and lignosulfonate (sulphur sources) with NaCl as template. At the same time the sulphonate group in the lignosulphonate as a sulphur source sulphurises the transition metal to binary metal sulfides. The (M 1, M 2 ) x S y @SNC has a large specific surface area (171.5 m 2 g −1 ), abundant defects and honeycomb-like hierarchical porosity with interconnected pore structures. The overpotential (at 10 mA cm −2 ) of the prepared (Fe, Ni)9 S8 @SNC was only 207 mV in 1 mol KOH. In this study, we provide a green and novel fabrication method for the synthesis of binary metal sulphides and achieves a high-value utilization of biomass. Graphical abstract: Image 1 Highlights: The synthesized (M1, M2 )x Sy @SNC has honeycomb-like hierarchical porosity with interconnected pore structures. Lignosulfonates were first used to prepare metal sulphides without other sulphur sources which is harmful to environment. The prepared (M1, M2 )x Sy @SNC has a lower overpotential than commercial IrO2 .